Legal Reconstruction of Criminal Regulation on the Cultural Tradition of Carrying Sharp Weapons as a Symbol of Nusantara Culture - Moh. Sawi (PT FORMOSA CENDEKIA GLOBAL, 2026)
Indonesia's cultural plurality includes long-standing traditions of carrying traditional weapons, such as nyikep (celurit) in Madura and badik in Bugis culture, symbolizing honor and self-defense. However, Article 2, paragraph (1) of Emergency Law No. 12/1951 strictly criminalizes this practice without a permit, leading to numerous judicial convictions. This creates a profound conflict between national positive law and the constitutional rights of customary law communities guaranteed under the 1945 Constitution of Indonesia. This legal disharmony poses philosophical, juridical, and sociological challenges, as existing regulations fail to accommodate traditional weapons as cultural identity. Consequently, indigenous people face criminal penalties while preserving their heritage. This study analyzes this legal friction, highlighting the urgency of integrating cultural recognition into national criminal justice policy framework.